2022
DOI: 10.1186/s13047-022-00542-7
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of podiatry service use for people with inflammatory rheumatic diseases: a review of a rheumatology podiatry clinic in Aotearoa New Zealand

Abstract: Background Foot problems, including foot pain, structural deformities, skin and nail lesions, and footwear difficulties, are common in people with inflammatory rheumatic diseases. However, dedicated podiatry services are limited, including in Aotearoa New Zealand. This study aimed to evaluate the podiatry service use for people with inflammatory rheumatic diseases who attended a specialist podiatric rheumatology clinic in Aotearoa New Zealand. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The most common reasons for people with RA to seek foot health services are foot pain, skin and nail lesions and footwear and orthotic needs [ 14 ]. However, there seems to be a discrepancy between foot health needs of people with RA and the care provided [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common reasons for people with RA to seek foot health services are foot pain, skin and nail lesions and footwear and orthotic needs [ 14 ]. However, there seems to be a discrepancy between foot health needs of people with RA and the care provided [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of foot health services among people with RA, previous studies [ 8 , 9 , 11 , 14 ] have reported their experiences of using foot health services. However, little is known about the perceptions of people with RA who do not use foot health services and their views on how foot health services could be developed to meet the foot health needs of people with RA.…”
Section: Introductionmentioning
confidence: 99%